Pethidine's Half-life Alterations following Orthopedic Surgery: Is Available Literature Always Compatible with the Data Obtained at the Bedside? - Shima Afhsar; Farshad Hashemian; Sasan Anari; Mahnaz Qomi; Mohammadreza Rouini (Research Center for Rational Use of Drugs (RCRUD), 2020)
Background:  It is suggested that surgery results in changes in kinetic profile of some medication. The aim of this study was to investigate possible alterations in pethidine's half-life in postoperative pain management following orthopedic surgery of the inferior limb. Methods: Twelve patients who were classified as class I patients according to the American society of anesthesiologists physical status classification were enrolled. Following the surgery of the lower limb, 25 mg of pethidine was injected intravenously. After that, 5, 30, 60 and 180 minutes following the injection, blood samples were taken and concentration of pethidine in blood samples were measured by High Performance Liquid Chromatography method. Moreover, patients' pain levels were assessed on visual analogue scales. Results: The average half-life of pethidine was measured to be 29.68 minutes. Thirty minutes after the injection, significant relationship between plasma levels of pethidine and pain scale was reported (p= 0.041, r= 0.595). Moreover, men were found to perceive more pain than women. Pain scale was considerably different between smokers and non-smokers (p= 0.006), although blood concentration of pethidine was not significantly different between these two groups (p=0.09). onclusions: Orthopedic surgery most probably results in alterations in pharmacokinetic profile of pethidine. Moreover, gender and smoking status of the patients influence pain perception. Thus, pharmacokinetic alterations due to inferior limb orthopedic surgery, gender-related factors and smoking status of the patients should be considered in pain management in clinical settings.